Health Monitoring and Identification of Tree Planting Plants in the Area of Campus Biodiversity Forest of State Islamic University of Maulana Malik Ibrahim, Malang - Winarto, Yoga Permadi; Harianto, Fitri; Djulkarnain, Wildi; Prahardika, Bayu Agung; Zahra, Elok Dzikrinina; Abida, Khumairoh Nur; Hazmi, Muhammad Rizal (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2024)
A forest is an ecosystem unit in the form of a stretch of land with natural resources dominated by trees with all their benefits for living things in the surrounding environment. The urgency of the presence of forest ecosystems encourages related to improving the quality of forest management with the aim of guaranteeing its functions and benefits. State Islamic University of Maulana Malik Ibrahim Malang is one of the actors in forest ecosystem management activities through campus forest areas with tree planting activities. In this study, it was intended to monitor and identify plant health using the Forest Health Monitoring (FHM) method. The samples observed in this study were 71 plants with tree species varying from longan new crystal (Dimocarpus longan), red jackfruit (Artocarpus heterophyllus), alligator avocado (Persea americana), and banyan tree (Ficus benjamina). The results showed that almost all of the samples belonged to the healthy class of the Tree Health Index, except for one sample which was found to have died. Some causes of tree damage include pest attacks in the form of insects and sooty mildew as well as spots and discoloration on leaves. Steps to anticipate more severe damage by carrying out maintenance and handling strategies in the form of improving irrigation techniques, embroidery techniques, cleaning pests and weeds, and fertilizing.